(untitled) (Marketing Journal, 2025)
This article analyzes the economic content of production investments in industrial enterprises, their structural structure and mechanisms of influence on production activities on a scientific basis. The author, having thoroughly studied various theoretical views on the concept of investment, reconsiders their role and significance in modern economic conditions. The article considers production investments not only as the main driver of economic growth and technological innovation, but also as a strategic re source that ensures the competitiveness of the enterprise. The main criteria and indicators for assessing investment efficiency (NPV, IRR, ROI, etc.) are also analyzed and recommendations are given for their effective application in practice. The article a lso substantiates the relevance of a systematic approach to managing production investments, dynamic modeling and taking into account institutional factors. Based on scientific and theoretical analyses, proposals are developed to increase the efficiency of investment activities.